PSIXOLOGIYA ILIMLERI КОНСТРУКТИВ ПСИХОЛОГИЯНИ ШАКЛЛАНТИРИШ ОМИЛЛАРИ - Файзиева, М. (SCIENCE and SOCIETY, 2022)
This article describes in detail the factors of formation of constructive psychology, the program of experimental work on the formation of constructive psychological protection of future psychologists, ways to effectively use the established diagnostic, theoretical and organized experimental blocks.
Keywords: constructive psychology; diagnostic; theoretical and organized experimental blocks; Plutchik-Kellerman-Conte survey; overall voltage of the protective system; psychological protection; coping behavior